Electrochemical and Mechanical characterization of Ni/SiC composite coatings electrodeposited on steel - Ghelani, L.; Boulahrouz, S.; Naoun, M.; Aissani, L (University of Eloued جامعة الوادي, 2018)
In this study, the structure (Ni/SiC) composite and pure nickel coatings were prepared by electroplating deposition on steel in a Watts bath of electroplating chloride, consisting of an electrolytic nickel matrix (binder) with and without adding silicon carbide micro particles (SiC) (mean diameter 0.8 m) which a high hardness and a good chemical stability. The coating analysis is performed by atomic force microscopy (AFM), and scanning electron microscopy (SEM). The characterizations of the deposited layers are carried out in 3.5% NaCl solution. The weight loss and the polarization results highlighted a silicon carbide concentration which can be included in the overall expression of a good composite coating. Moreover, the incorporation of the micro particles had a significant impact on the micro hardness of the composite deposits (Ni / SiC).
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: electrodeposition, co-deposition, SiC, weight loss, polarization